Information literacy on the dangers of Covid-19 in Serang City - Iman Mukhroman; Rangga Galura Gumelar (Jurnal Kajian Informasi dan Perpustakaan, 2022)
The rapid spread of information on the dangers of Covid-19 through social media is not directly proportional to the accuracy of the truth of the current news. People believe in various categories of hoax news developed in the community that cannot be justified. The public must control information literacy in this uncertain condition. This study examined information literacy about the dangers of Covid-19 in the community in Serang City, Banten Province. Method research used a quantitative approach with survey methods and also field observations. The sample in this study was 100 respondents spread over six sub-districts in Serang City. The study results showed that 75% of the people of Serang City used social media, meaning that the people of Serang City had the characteristics of an information society and were technology literate. People as many as 42% stated that they obtained most of the news related to Covid-19 from Facebook. It also discovered that people of 10% of Serang City's people could not choose and analyze news related to Covid-19, whether it was a hoax or genuine. People tended to share the news they received without checking first. News related to the dangers of Covid-19, which the government spread on conventional media and social media, did not change people's patterns and attitudes much. People were more likely to believe in beliefs and cultural values that were considered correct. This condition concludes that information literacy about the dangers of Covid-19 in the people of Serang City still needs improvements.